2018
DOI: 10.1177/0891243217750119
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Gendered Entrepreneurial Subject: Gender, Development, and the Informal Economy in India

Abstract: Challenging the gendered entrepreneurial SubjeCt gender, development, and the informal economy in india Natascia Boeri Bloomfield college, Usa the World Bank's premise that "gender equality is good business" characterizes the current gender and economic development model. Policymakers and development practitioners promote and encourage women's entrepreneurialism from the conviction that increasing women's market-based opportunities is key to lifting women, their families, and communities out of poverty, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 42 publications
0
43
0
1
Order By: Relevance
“…Women OMEs running high-tech ventures are therefore perceived and categorized by the media as being different and perhaps more "entrepreneurial" than those in other sectors. (Boeri, 2018). Women's empowerment can have a positive impact on society's perception of women OMEs' role in developing the economy and thus minimize cultural barriers.…”
Section: --------------------------mentioning
confidence: 99%
“…Women OMEs running high-tech ventures are therefore perceived and categorized by the media as being different and perhaps more "entrepreneurial" than those in other sectors. (Boeri, 2018). Women's empowerment can have a positive impact on society's perception of women OMEs' role in developing the economy and thus minimize cultural barriers.…”
Section: --------------------------mentioning
confidence: 99%
“…Some single-country studies have demonstrated that mothers are pulled into self-employment to meet intensive mothering ideals, whilst avoiding the stigmatization of being a housewife (Bjuggren & Henrekson, 2018;Ekinsmyth, 2011;Patrick et al, 2016). In South Asia, Boeri (2018) and Kabeer (2000) show that home-based self-employment does not carry the same stigma as factory work,…”
Section: The Mumpreneurship Thesismentioning
confidence: 99%
“…After interviewing 60 self‐employed mothers in Australia, they conclude entrepreneur‐mothers’ motives for choosing self‐employment include the moral importance of (intensive) mothering, experienced time‐related conflicts and constraints in dependent employment, and perceptions that the available career options for mothers in organizational employment are intellectually unchallenging (Foley et al, 2018). Home‐based self‐employment has also been reported to be a work choice that does not violate gender norms against working mothers, nor against stay‐at‐home mothers (Bjuggren & Henrekson, 2018; Boeri, 2018; Kabeer, 2000). The mumpreneurship literature thus considers self‐employment to occupy the middle ground between home‐making and dependent employment through the more flexible organization of both time and income, as well as enabling women to fulfil conflicting obligations as good mothers and good workers (Boden, 1999; Carr, 1996; Ekinsmyth, 2011; Simoes et al, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Stove-sector programmes thus closely follow the Women in Development initiatives of the 1970s, where gender vulnerability became a cornerstone for intervention by international development agencies (Ghertner, 2006); an ambition that has since gained traction with the 2000 Millennium Development Goals followed by the more recent United Nations' Sustainable Development Goals. The emergence of the Global Alliance for Clean Cookstoves (GACC) in 2010 has carried the women's empowerment mantle forward (Goetz and Jenkins, 2016;Simon et al, 2014) and follows broader considerations of empowerment within rural development settings (Alkire et al, 2013;Alsop et al, 2005;Kabeer, 1999;Kabeer et al, 2013;Kishor and Subaiya, 2008) and informal, household work contexts (Boeri, 2018;Bose, 2007;Kantor, 2003). Within the clean cookstove sector, the objective of women's economic empowerment is presented as straightforward and uncontroversial.…”
Section: Women's Empowerment In the Clean Cookstove Sectormentioning
confidence: 99%